2019
DOI: 10.1124/dmd.118.085977
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Naloxone and Naltrexone Following Intranasal Administration to Healthy Subjects

Abstract: Naloxone (17-allyl-4,5a-epoxy-3,14-dihydroxymorphinan-6-one HCl), a m-opioid receptor antagonist, is administered intranasally to reverse an opioid overdose but its short half-life may necessitate subsequent doses. The addition of naltrexone [17-(cyclopropylmethyl)-4,5a-epoxy-3,14-dihydroxymorphinan-6-one], another m-receptor antagonist, which has a reported half-life of 3 1/2 hours, may extend the available time to receive medical treatment. In a phase 1 pharmacokinetic study, healthy adults were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…However, sublingual absorption of naloxone might be greater than originally thought 30 . There is no apparent evidence that either naltrexone or naloxone is transported by p‐glycoprotein, 31 but it has been suggested that naloxone and fentanyl may share a cellular membrane transporter 28 . This transporter may become saturated at high doses and plasma concentrations of fentanyl, reducing the blood‐brain barrier transport of naloxone 28 …”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, sublingual absorption of naloxone might be greater than originally thought 30 . There is no apparent evidence that either naltrexone or naloxone is transported by p‐glycoprotein, 31 but it has been suggested that naloxone and fentanyl may share a cellular membrane transporter 28 . This transporter may become saturated at high doses and plasma concentrations of fentanyl, reducing the blood‐brain barrier transport of naloxone 28 …”
Section: Commentmentioning
confidence: 99%
“…The plasma half‐life of naloxone is about 8.3 hours, that of nalmefene 1.3 h, but the brain residency time of nalmefene might be significantly longer than that of naloxone 32 . Naltrexone has a plasma half‐life of approximately 3.5 h, 31 but brain residency 72 to 108 h 32 . This suggests that naltrexone might be a better option for opioid overdose, although to date little data have been generated to prove this point.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Naloxone has a comparably short half‐life and duration of action of around 60‐90 minutes. whereas many opioids have a longer half‐life or are formulated as sustained‐release preparations, which may require additional naloxone doses and close monitoring of the patient 174 . In addition, naloxone and other competitive opioid‐receptor antagonists may require a higher dose to overcome highly potent opioid agonists, such as fentanyl analogues and buprenorphine 91,175 .…”
Section: Treatmentmentioning
confidence: 99%
“…Naltrexone is also approved for the treatment of opioid use disorders, most recently as an intramuscular depot formulation (Lee et al, ; Woody & Metzger, ). Very recent studies have also examined whether novel formulations of naltrexone or nalmefene could be useful as potent and long‐lasting medications against overdose caused by μ‐agonists such as fentanyl (Krieter, Chiang, Gyaw, Skolnick, & Snyder, ; Krieter, Gyaw, Crystal, & Skolnick, ).…”
Section: Introductionmentioning
confidence: 99%